Luxury fashion brand management and sustainability : unifying fashion with sustainability - Mitterfellner, Olga, 1978- (Mastering fashion management, 2023)
"This textbook examines fashion luxury brand management, providing students with a comprehensive understanding of its origins, unique components, current practices, global trade and most importantly, the application of sustainable models to the industry. It also highlights what makes brands fail and how they can become more resilient. The key content covers the heritage of luxury brands, the importance of craftsmanship and creative direction, the role of luxury conglomerates, cultural awareness and internationalisation, risks of failure and opportunities for revitalisation as well as the application of sustainable measures for a resilient and ethical brand future. Each chapter includes a combination of industry insights, case studies or expert interviews. Coupled with theory frameworks and business models, these examples and case studies show how sustainable models can be applied to existing luxury brands and how practices can be embedded into the brand concept. Students are encouraged to think about opportunities and solutions, unique to luxury brand management, and will gain knowledge and skills for a successful future career. A truly global and holistic textbook, Luxury Fashion Brand Management and Sustainability should be core and recommended reading for advanced undergraduate and postgraduate students studying Luxury Fashion Management, Luxury Brand Management, Sustainable Fashion and Responsible Business, Fashion Marketing and Communications. Supplementary online resources include chapter-by-chapter PowerPoint slides and a test bank"--